The Relationship between Socioeconomic Status, Family Income, and Measures of Muscular and Cardiorespiratory Fitness in Colombian Schoolchildren (2017)
Objective To determine the associations between socioeconomic status (SES) and physical fitness in a sample of Colombian youth. Study design Prueba SER is cross-sectional survey of schoolchildren in Bogota, Colombia. Mass, stature, muscular fitness (standing long-jump, handgrip), and cardiorespiratory fitness (20-m shuttle run) were measured in 52 187 schoolchildren 14-16 years of age. Area-level SES was categorized from 1 (very low) to 4 (high) and parent-reported family income was categorized as low, middle, or high. Results Converting measures into z scores showed stature, muscular, and cardiorespiratory fitness were significantly (z = 0.3-0.7) below European values. Children in the mid- and high SES groups jumped significantly further than groups with very low SES. Differences were independent of sex but became nonsignificant when adjusted for anthropometric differences. Participants in the mid-SES and high-SES groups had better handgrip scores when adjusted for body dimension. There were, however, no significant between-group differences in cardiorespiratory fitness, which was strongly clustered by school and significantly greater in students from private schools. Conclusions Area-level SES is associated with measures of muscular fitness in Colombian schoolchildren. These associations were largely explained by the large differences in body dimensions observed between SES groups. When area-level SES is considered, there was no evidence that family income influenced fitness. The clustering of outcomes reaffirms the potential importance of schools and area-level factors in promoting fitness through opportunities for physical activity. Interventions implemented in schools, can improve academic attainment; a factor likely to be important in promoting the social mobility of children from poorer families. © 2016 Elsevier Inc.